Introduccion del principio de continuidad laboral en el codigo del trabajo - Yangora Nawech, Benito Estanislao (2017)
As of October 20, 2008 the country has a new constitution of the Republic, the same as the Constitutionalist scholars have said it has a character of "guarantor" of the rights of persons and the legislature assigned rights to the nature, in particular, which is something new in the world. We actually have a new legal-political state system, that will take some time to develop and strengthen institutional arrangements as a true modern state; we must have patience and patriotism we'll be forged steadily in the course of time. Article 1 of the Constitution provides that: "Ecuador is a constitutional State of rights and justice, (...)". Special interest aroused in me to learn more and deepen the study of the rights and principles that protect, especially the worker, and relating to the principle of continued employment; in order to determine whether or not these are known by the worker to the employer can demand respect and compliance with the Constitution and the law. This was the reason to raise the theme of this important legal research discussed later. That has been a work in one way or another has confirmed that although the Constitution of the Republic of Ecuador and the Labour Code contained legal provisions which reaffirm the recognition of the fundamental principles of work are as they are: protective principle, the continuity of the employment relationship, the primacy of reality, reason ability, irrevocable labor rights, freedom of association, etc .; the fact remains that these principles are trasgredidos again and again, being an obligation and duty of the State, ensure Ecuadorians the full enjoyment of the rights recognized in the Constitution, as is the right to work and principles protect this right. If you talk about work, we mean necessarily any manual or intellectual activity performed by human beings, that generates income (compensation), which serve to meet their needs and those of your family. The provision of services or performance of a work that is performed by the employed or directed by the employer, giving rise to the employment relationship and thus the existence of an employment contract is verbal or written, the same as is tract thereafter, presenting a characteristic residence to extinction, either by death, retirement worker for the expiration of the agreed term, or for other good cause; keeping in mind the idea that the worker is to respect the principle of continuity of employment or job security; important aspect which translates into economic and psychological safety of the worker, to have a fixed occupation and fixed income. But looking at the reality that workers face in Ecuador, it has been shown that it is quite common that or employers, violating the laws, breach of the principle of continuity of employment and job security act It expresses provision against legal and arbitrary, unilateral and suddenly they terminate the employment contract, ie intempestivamente fire workers or workers. It has been also observed that the constant norms in the Labour Code and that refer to unfair dismissal, not a "threat" to the employer do not constitute "coercion" that in one way or another being forced to fulfill their obligations , hence, the principle of continuity, one of the fundamental rights which must be incorporated in the Labour Code, to respond positively to reality; and against unfair dismissal and so there is a real legal guarantees which protect the worker, taking into account the legal and social importance of work for the development of Ecuador, of Ecuadorians.